Library of Samples for E-Vehicle Propulsion Drive Tuning - Rassõlkin, Anton; Liivik, Liisa; Vodovozov, Valery; Raud, Zoja (Electrical, Control and Communication Engineering, 2014)
The majority of testing cycles for the vehicle comparison is the long-term cycles and could not be used for the short-term transient mode imitations. Also, all the used nowadays testing cycles were designed for internal combustion engine vehicles and take into account not only energy and mechanical aspects, but also pollution and internal combustion engine characteristics. The paper presents a collection of sample signals developed to explore and simulate multiple system impacts to emulate different reference and load conditions. The study describes the major driving modes, such as the constant-speed cruising, speeding up and braking, typical parking regimes, uphill and downhill motion, and taking a turn. The developed testing equipment and software are described. Responses of the battery vehicle drives to the changeable controls and disturbances were studied in the laboratory test bench. The set of test cycles prepared in the frame of the ABB control arrangement was applied to the system evaluation and assessment. The developed methodology can be recommended to adjust the electric drives for different kinds of testing equipment. Experimental validation of the described approach has demonstrated the broad possibilities for the steady-state and transient modes of vehicle quality evaluation. It suits for recommendations that can be made with regard to the tuning of the drive regulators, control looping, sensor allocation, and feedback arrangements.